2019
DOI: 10.1038/s41893-019-0415-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating crop yield losses through weed diversity

Abstract: Concilier la productivité des cultures et le maintien de la biodiversité est l'un des principaux défis de l'agriculture mondiale. Nous avons testé les hypothèses selon lesquelles (i) toutes les communautés adventices ne génèrent pas de pertes de rendement et (ii) que des communautés adventices plus diversifiées peuvent atténuer les pertes de rendement. L'étude est basée sur trois années d'observations des densités et biomasses adventices à quatre stades critiques de croissance des céréales d'hiver dans 54 zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 59 publications
5
117
0
7
Order By: Relevance
“…This result is consistent with many studies (e.g. Bybee-Finley, Mirsky & Ryan, 2017; Adeux et al , 2019), which also find a negative relationship between crop productivity and weed biomass, and it suggests that crops and weeds compete for the same resources and hinder each other’s performances. The effects of our ecotype treatment on crops and weeds supports this idea: the Swiss ecotypes showed higher yield, but also lower weed diversity and biomass compared to the Spanish varieties (Fig S1 of SI, Table 2).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with many studies (e.g. Bybee-Finley, Mirsky & Ryan, 2017; Adeux et al , 2019), which also find a negative relationship between crop productivity and weed biomass, and it suggests that crops and weeds compete for the same resources and hinder each other’s performances. The effects of our ecotype treatment on crops and weeds supports this idea: the Swiss ecotypes showed higher yield, but also lower weed diversity and biomass compared to the Spanish varieties (Fig S1 of SI, Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…These two weed species thrive on nitrogen-rich soils, particularly Echinochloa , which can remove available soil nitrogen by up to 80% and thereby significantly reduce crop yield (Randall, 2012; Heuzé, 2017). Weed evenness can consecutively influence crop yield: increasing weed community evenness decreases weed biomass and increases crop productivity (Adeux et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Yield loss is then estimated as the difference of the yield in the different zones or fields relative to the maximum observed yield, and then linked the yieldloss estimation to a series of weed flora variables (e.g., plant densities, biomass). But simple weed metrics are not sufficient to explain yield loss as recent field studies reported that yield loss decreases with increasing diversity and richness in the weed community (Storkey and Neve, 2018;Adeux et al, 2019b).…”
Section: How Crop: Weed Interference Is Quantifiedmentioning
confidence: 99%
“…Both events can lead to underestimating potential yield. The best way to estimate yield losses at the annual scale consists in comparing the yield in weedy zones to that in weedfree controls without chemical or mechanical weeding (Adeux et al, 2019b). Indeed, mechanical weeding is also likely to affect crop growth, e.g., through modification in the nitrogen dynamics (Gilbert et al, 2009) or by uprooting crop plants (Rasmussen et al, 2009).…”
Section: How Crop: Weed Interference Is Quantifiedmentioning
confidence: 99%
“…While seedbank sizes are of primary concern, the seedbank composition can provide insight into weed dynamics and differences in composition can be used to assess the relative strength of the filters defining the weed community (e.g., Ryan et al, 2010). Additionally, there is some evidence that crop yield loss and weed diversity are negatively correlated (Adeux et al, 2019) and more diverse assemblages of weed seeds in the soil may reflect the impacts of more sustainable management strategies (Storkey and Neve, 2018). Information about the size and composition of weed seedbanks after two or more full crop rotation sequences may therefore provide a more complete picture of weed responses to cover cropping.…”
Section: Introductionmentioning
confidence: 99%